Microbial Murders Crime Scene Investigation: An Active Team-Based Learning Project that Enhances Student Enthusiasm and Comprehension of Clinical Microbial Pathogens - J. Jordan Steel (American Society for Microbiology, 2017)
Microbial disease knowledge is a critical component of microbiology courses and is beneficial for many students’ future careers. Microbiology courses traditionally cover core concepts through lectures and labs, but specific instruction on microbial diseases varies greatly depending on the instructor and course. A common project involves students researching and presenting a disease to the class. This method alone is not very effective, and course evaluations have consistently indicated that students felt they lacked adequate disease knowledge; therefore, a more hands-on and interactive disease project was developed called Microbial Murders. For this team-based project, a group of students chooses a pathogen, researches the disease, creates a “mugshot” of the pathogen, and develops a corresponding “crime scene,” where a hypothetical patient has died from the microbe. Each group gives a presentation introducing the microbial pathogen, signs/symptoms, treatments, and overall characteristics. The students then visit each other’s crime scenes to match the pathogen with the correct crime scene by critically thinking through the clues. This project has shown remarkable success. Surveys indicate that 73% of students thought the project helped them understand the material and 84% said it was worth their time. Student participation, excitement, understanding, and application of microbial disease knowledge have increased and are evident through an increase in course evaluations and in student assessment scores. This project is easy to implement and can be used in a wide variety of biology, microbiology, or health classes for any level (middle school through college).